Ontology and semiosis: Ways of Being and Meaning in "Larva. Babel de una noche de San Juan" - Núñez Cantos, Marco Antonio (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
In this paper we try to make explicit the philosophical ideas that operate in critical approaches based on the «mimesis» Aristotelian, from the novel Larva. Babel de una noche de San Juan (1983), by Julián Ríos, a novel that problematizes the notion of literature built on the following assumptions: (1) the extra-linguistic referent is the generator of meaning, and (2) there is an immediate presence of entities to the consciousness of the subject. Both prejudices sediment the realistic canon. The breaking of Ríos’s novel the discrete character of the signifier and continually referring to other texts of the tradition, manifests its nature as a verbal artifact and questions both the generating capacity of the referent, as well as the presupposition of an ontology of presence, and, consequently , the entire critical tradition of the West.